The possibility of claim for collective damage by associations and Non-Government Organizations (NGOs) (With a comparative study on French law) - Saeid Bighdeli; Ahmad Ekhtiyari (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2018)
Collective loss which in its general sense includes losses suffered by the whole members of a set and in its special sense is the loss incurred on the totality of a set, without it necessarily contains the detriment of the individual members,has today drawn the attention of different countries' law for various reasons. In the meantime, one of the basic questions, is the possibility of its claim by collective legal personality. Despite the importance of this subject and the necessity of determining its legal status, sufficient attention has not been paid to it in domestic laws; and judicial precedent has no specific judgment in this regard. This writing,meanwhile the attempt to study the subject in the accepted framework of rules and regulations governing the law of Iran, has tried to study it in French Law and taken its generalization to Iran's law into accounts. Accordingly, it seems, despite the current differences in the two legal systems in terms of legislation and case law, the law of Iran can also enjoy its present legal potentialities to move toward opening the ways of accepting this claim in its domestic law, as France did.